Pengaruh Sistem Informasi Akuntansi terhadap Efektivitas Transaksi E-Business di indonesia - Icha Riani; Rayyan Firdaus (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
Accounting Information Systems (AIS) play an important role in supporting the effectiveness of e-business transactions, especially in a business environment that is increasingly dependent on digital technology. This research aims to examine the influence of AIS on the effectiveness of e-business transactions in Indonesia, with a focus on aspects of speed, accuracy and security of transactions. The research method used is a survey with a quantitative approach, where data is obtained through questionnaires distributed to e-business actors in various industrial sectors. The research results show that the use of integrated AIS can increase operational efficiency, reduce transaction recording errors, and increase transparency in financial reporting. Apart from that, SIA also contributes to increasing customer trust through a safer and more reliable system. The implications of this research show that good AIS implementation is crucial in supporting the sustainability and effectiveness of e-business transactions, so it is hoped that it can become a reference for companies that want to optimize their e-business performance.